Draft Annual Plan 1987-88 Vol. III (In 4 Volumes) Haryana State - Planning Commission (Planning Commission, 1986)
An outlay of Rs. 41850 lakhs was approved in the draft VII Five year Plan for Major Medium and Multipurpose River Valley Projects. Out of this Rs. 41862 lakhs is for major medium irrigation schemes, and Rs. (-) 12 lakhs for Multipurpose River Valley Projects viz. Unit I & II of the Beas Project the work on the Beas Project Unit I & II has been practically completed, as such a nominal provision of Rs. (-) 12 lakhs was made to account for Haryana's share receipts from this project under Irrigation Component. A provision of Rs. (-)7 lakhs had been made during 1985-86 for this work. Provision during 1987-88 has been proposed as Rs. (-)2 lakhs.
Planning Department, Government of Haryana